Pengaruh Modal Kerja dan Biaya Operasional Terhadap Laba Bersih - Purwanti; Umdatun Rismasari, Apriliana (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To examine the effect of working capital and operating costs on net profit either partially or simultaneously. Background Problems: Management of the company's working capital so that it can work optimally to be able to generate maximum profits as well, as well as how the company can best manage operational costs effectively and efficiently to get maximum company profits. Novelty: Re-examining previous research, namely working capital variables and operational costs on working capital with different companies. Research Methods: Using a purposive sampling method on 16 companies with the highest working capital on the IDX. Finding/Results: Partially, working capital has a positive and significant effect on net income, while operational costs have no significant effect on net income, and simultaneously working capital and operational costs have a significant effect on net income. Conclusion: Operational costs cannot be used as a factor in making decisions related to increasing net profit even though these costs are closely related to the company's operational activities.